2019
DOI: 10.3390/agronomy9020054
|View full text |Cite
|
Sign up to set email alerts
|

Biomass Prediction of Heterogeneous Temperate Grasslands Using an SfM Approach Based on UAV Imaging

Abstract: An early and precise yield estimation in intensive managed grassland is mandatory for economic management decisions. RGB (red, green, blue) cameras attached on an unmanned aerial vehicle (UAV) represent a promising non-destructive technology for the assessment of crop traits especially in large and remote areas. Photogrammetric structure from motion (SfM) processing of the UAV-based images into point clouds can be used to generate 3D spatial information about the canopy height (CH). The aim of this study was t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

12
131
1
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 84 publications
(145 citation statements)
references
References 38 publications
12
131
1
1
Order By: Relevance
“…Plant height is another widely used structural and physical parameter used to estimate the biomass of various crops [20,23,53,54]. Previous studies on grasslands indicated moderate to high correlation (R 2 = 0.59-0.81) on predicting dry herbage yield from plant height measurements [45]. In the current study, the R 2 of plant height vs. log-transformed DHY was more variable (R 2 = 0.12-0.65) than NDVI across seasons.…”
Section: Discussionmentioning
confidence: 45%
See 1 more Smart Citation
“…Plant height is another widely used structural and physical parameter used to estimate the biomass of various crops [20,23,53,54]. Previous studies on grasslands indicated moderate to high correlation (R 2 = 0.59-0.81) on predicting dry herbage yield from plant height measurements [45]. In the current study, the R 2 of plant height vs. log-transformed DHY was more variable (R 2 = 0.12-0.65) than NDVI across seasons.…”
Section: Discussionmentioning
confidence: 45%
“…The seasonal HY distribution in the 2017 and 2018 showed that HY from the 2017 harvest dates was higher compared to 2018 in all seasons. The notable decline in dry matter yield as the year progressed may result from the drought stress and repetitive cutting [45].…”
Section: Discussionmentioning
confidence: 99%
“…> 1ha) and the spatial coverage is limited, TLS approaches are not appropriate for large-scale estimation of grassland yield. To derive point clouds, photogrammetric approaches based on numerous photographs from different viewing angles might be an alternative (Wijesingha et al 2019, Grüner et al 2019, Forsmoo et al 2018, Viljanen et al 2018, Bareth, Schellberg 2018 to TLS measurements. While point clouds created from TLS have a deeper penetration into the grassland canopy and can also be affected by single plant parts sticking out (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…height measurements or the rising plate meter) can also be affected by the canopy structure and are not applicable on large fields. To compensate for this effect, SfM approaches have been proven to deliver equal or even better yield estimations than traditional field methods (Grüner et al 2019, Bareth, Schellberg 2018. For example, Grüner et al 2019 showed an improved prediction quality (i.e.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation